Effect of gastrin on liver regeneration after partial hepatectomy in rats. Issue 1 (January 1990) - Rasmussen, T N; Jørgensen, P E; Almdal, T; Poulsen, S S; Olsen, P S
Abstract : Gastrin has been shown to be an important trophic hormone for the mucosa of the stomach and the proximal intestine. In the present study the effect of gastrin on liver regeneration after partial hepatectomy in rats was investigated. After partial hepatectomy a significant rise in the concentration of gastrin in portal venous blood was found six, 12, and 18 hours after 70% hepatectomy. The effect of changes in the endogenous gastrin concentration on the liver regeneration was investigated in rats subjected to antrectomy or to fundectomy. Partial hepatectomy was done three weeks after the primary surgery. We found antrectomy to decrease liver regeneration, whereas fundectomy had no effect. Administration of pentagastrin 300 micrograms/kg sc three times daily for two and four days after partial hepatectomy significantly increased the rate of liver regeneration compared with controls. This study suggests that gastrin has a hepatotrophic effect. Whether this effect is caused by a direct action of gastrin on the hepatocytes or it is an indirect effect mediated by for instance insulin, glucagon or epidermal growth factor has to be further investigated.